2023
DOI: 10.1192/j.eurpsy.2023.4
|View full text |Cite
|
Sign up to set email alerts
|

In vivo serotonin 1A receptor hippocampal binding potential in depression and reported childhood adversity

Abstract: This peer-reviewed article has been accepted for publication but not yet copyedited or typeset, and so may be subject to change during the production process. The article is considered published and may be cited using its DOI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 85 publications
(174 reference statements)
0
1
0
Order By: Relevance
“…Conversely, a review by Shrestha et al [78] reported that among the eight studies they reviewed on 5-HT1A expression in the brains of patients with MDD, four demonstrated a decrease in 5-HT1A receptor density, two showed no change, and only two indicated an increase in 5-HT1A receptor density. Furthermore, Bartlett et al [79] found no correlation between the severity of a depressive episode and an increase in 5-HT1AR binding potential. Another study indicated a decrease in the expression of 5-HT1A in the reserpine model of depression in rats [80].…”
Section: Receptormentioning
confidence: 98%
“…Conversely, a review by Shrestha et al [78] reported that among the eight studies they reviewed on 5-HT1A expression in the brains of patients with MDD, four demonstrated a decrease in 5-HT1A receptor density, two showed no change, and only two indicated an increase in 5-HT1A receptor density. Furthermore, Bartlett et al [79] found no correlation between the severity of a depressive episode and an increase in 5-HT1AR binding potential. Another study indicated a decrease in the expression of 5-HT1A in the reserpine model of depression in rats [80].…”
Section: Receptormentioning
confidence: 98%